An approach using heuristic pheromones-based ACO modelling for green vehicle routing optimisation. (14th June 2022) - Prakash, Ravi; Pushkar, Shashank
A mathematical heuristic-based method was introduced for addressing the issue in green vehicle routing optimisation (GVRO). It analyses a large number of vehicles along with a limited refuelling network. A standard solution to this problem is given in this paper. GVRO seeks to minimise travel time renewable fuel sources while ensuring fewer emissions from greenhouse gases. An effective algorithm relies on a branch/slice optimisation algorithm that combines a variety of valid inequalities in exams to increase lower limits. Implementation of an optimisation algorithm based on heuristic ant colony optimisation (ACO) to obtain the best routes. In addition, the GVRO is better able to handle an accident and eliminates pollution by using the best alternatives.